Escaping into Sexual Play: A Consumer Experience Perspective. (1st July 2020) - Piha, Samuel; Hurmerinta, Leila; Järvinen, Elina; Räikkönen, Juulia; Sandberg, Birgitta
Abstract: Sexual play may offer an escape from everyday stress. As the consumer culture has extended into our bedrooms, escapism through sexual play can be regarded as an affective consumer experience. This study analyses how experiential value is created through escapism in sexual play enabled by the use of sex toys. The study follows a mixed-methods strategy, combining results from a consumer survey (n = 517) with expert interviews (n = 26). A principal outcome is an advanced conceptual framework where playfulness operates as a dynamic motor for consumers' sexual boundary transgressions. Loosening these sexual boundaries may have its downsides. The larger is the realm of regular sexual life, the harder it is to escape it to gain experiential value. The balance between sexual play and everyday life ensures that the dynamic motor of playfulness operates steadily, upkeeping the elasticity of boundaries. The practical implications are discussed.